Improving Access to Health Care Services through the Expansion of Coverage Program : The Case of Guatemala - Lao Pena, Christine (World Bank, Washington DC, 2013)
Since the signing of the 1996 Peace Accords, Guatemala has made efforts to establish economic and political stability, and to improve its social indicators. The country's Constitution states that access to health care is a basic right of all Guatemalans. In practice, however, it has been challenging for the Government of Guatemala to guarantee this right using public facilities. As a result, it has been trying to improve access to health services using both Ministry of Public Health and Social Assistance (MOH) facilities and staff, and alternative health service providers, particularly nongovernmental organizations (NGOs). This case study reviews the experience implementing the Expansion of Coverage Program (Programa de Extension de Cobertura, PEC) that was established by the Government of Guatemala in 1997 to improve coverage of health and nutrition services to poor, rural, and largely indigenous areas by contracting NGOs. It describes its origins; its package of services; contracting, financing, monitoring, and supervision mechanisms; and its contributions to improving access and strengthening primary health care services in Guatemala. It also discusses opportunities and challenges that need to be addressed to continue to improve health services coverage in the country.